2021
DOI: 10.21474/ijar01/12987
|View full text |Cite
|
Sign up to set email alerts
|

Reponse a La Fertilisation Organique Et Minerale De Deux Varietes De Gombo (Abelmoschus Esculentus (L) Moench, Malvacea) a Daloa, Cote Divoire

Abstract: This study aims to assess the effect of variety and organic and mineral fertilization on the agronomic parameters of okra. The experimental set-up used was a completely randomized en bloc device. The treatments used are : T0 (controls without amendment), T1 (10 t / ha of chicken manure), T2 (10 t / ha of sawdust, T3 (2.5 t / ha of NPK 15-15 fertilizer) -13). The two varieties compared are the improved variety called Clemson spineless and the local variety Koto or Soudais or gombo Baoule. The results obtained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, Kouayet et al, (2021) on the study l'Effets des amendements sur les caractéristiques agromorphologiques et sur l'entomofaune d'Abelmoschus esculentus (L) Moench. (Malvaceae) in Ngaoundéré (Cameroon) and Kouame et al, (2021) on the study of the Response to organic and mineral fertilization of two okra varieties (Abelmoschus esculentus (L) Moench, Malvacea) in Daloa, Côte d'Ivoire have shown that good yield also depends on fertilization. Sadak et al, (2013) also showed that okra grown in the presence of compost substrates has a positive impact on A. esculentus fruit yield.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kouayet et al, (2021) on the study l'Effets des amendements sur les caractéristiques agromorphologiques et sur l'entomofaune d'Abelmoschus esculentus (L) Moench. (Malvaceae) in Ngaoundéré (Cameroon) and Kouame et al, (2021) on the study of the Response to organic and mineral fertilization of two okra varieties (Abelmoschus esculentus (L) Moench, Malvacea) in Daloa, Côte d'Ivoire have shown that good yield also depends on fertilization. Sadak et al, (2013) also showed that okra grown in the presence of compost substrates has a positive impact on A. esculentus fruit yield.…”
Section: Discussionmentioning
confidence: 99%